2019
DOI: 10.3389/fmolb.2019.00103
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Challenges of Backbone, Sidechain, and RDC Experiments to Study Membrane Protein Dynamics in a Detergent-Free Lipid Environment Using Solution State NMR

Abstract: Whereas solution state NMR provided a wealth of information on the dynamics landscape of soluble proteins, only few studies have investigated membrane protein dynamics in a detergent-free lipid environment. Recent developments of smaller nanodiscs and other lipid-scaffolding polymers, such as styrene maleic acid (SMA), however, open new and promising avenues to explore the function-dynamics relationship of membrane proteins as well as between membrane proteins and their surrounding lipid environment. Favorably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 152 publications
0
9
0
Order By: Relevance
“…Polymer, saposin, and peptide nanodiscs are less rigid, but the size of the nanodisc particles is less homogeneous. ,,,, This is caused by a discontinuous saposin or peptide belt around the lipid nanodisc or by the polydispersity of the used polymers. Although the average size of these nanodiscs can be adjusted by changing the molar ratio of scaffold material and lipid molecules, the size control is less well understood than with MSP nanodiscs.…”
Section: Lipid Nanodiscsa Lipid-based and Native-like Membrane Mimeticmentioning
confidence: 99%
See 3 more Smart Citations
“…Polymer, saposin, and peptide nanodiscs are less rigid, but the size of the nanodisc particles is less homogeneous. ,,,, This is caused by a discontinuous saposin or peptide belt around the lipid nanodisc or by the polydispersity of the used polymers. Although the average size of these nanodiscs can be adjusted by changing the molar ratio of scaffold material and lipid molecules, the size control is less well understood than with MSP nanodiscs.…”
Section: Lipid Nanodiscsa Lipid-based and Native-like Membrane Mimeticmentioning
confidence: 99%
“…Nuclear magnetic resonance (NMR) spectroscopy is a powerful technique to obtain structural and dynamical insights on biomolecules at atomic resolution. In contrast to other structural techniques, solution-state NMR can probe structural and dynamical features of biomolecules in a native soluble form. This also holds true for MPs, where the properties and fluidity of the membrane environment are important factors for functionality. ,,,, However, due to the inherent physical limitations of the method, structure determination by solution-state NMR is currently limited to an approximate size range of 40–50 kDa. Nonetheless, it has been shown that solution-state NMR can be used to probe dynamics and conformational features of large (membrane) proteins up to 100 kDa to 1 MDa in size, utilizing specific methyl labeling of the proteins. , With such a strategy, NMR can be very efficiently used in a complementary manner in concert with X-ray crystallography and cryo-EM. The specialty of NMR is the structure determination of small and dynamic MPs, probing the dynamical features of MPs and monitoring the structural and dynamical effects of ligand binding.…”
Section: Solution-nmr Studies Of Mps In Nanodiscsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nanodiscs have also been used for structural studies of membrane proteins in a detergent‐free lipid environment by NMR 45,119,120 . Although the large sizes of Nanodiscs often put limitations on high resolution NMR spectroscopy in solution, the advantages of this method of membrane protein solubilization can be used by applying new experimental tools to solve this problem 121 .…”
Section: Introductionmentioning
confidence: 99%